2012
DOI: 10.1111/j.1440-172x.2012.02049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the contact isolation application on anxiety and depression levels of the patients

Abstract: This study was aimed to assess the effects of contact isolation application on anxiety and depression levels of the patients, the effects of certain sociodemographics and patient characteristics on anxiety and depression levels, and the thoughts of the isolated patients about contact isolation. This non-randomized quasi-experimental study was carried out with 60 isolated and 57 non-isolated patients with hospital infection. The data were acquired from Hospital Anxiety and Depression Scale (HADS-A (anxiety) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
1
32
0
1
Order By: Relevance
“…A total of 3879 papers were retrieved from the three databases; of which, 38 were assessed for eligibility by reading the full text. Of these, 13 studies provided data suitable for the calculation of risk ratio (RR), 5 giving psychological outcomes17–21 and 12 non-psychological19 22–32; and 8 provided data for the calculation of standardised mean differences (SMD), 6 giving psychological outcomes21 30 33–36 and 2 non-psychological 29 37. Further six studies did not provide raw data but are included in the results; three each giving psychological outcomes38–40 and non-psychological outcomes 17 41 42.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 3879 papers were retrieved from the three databases; of which, 38 were assessed for eligibility by reading the full text. Of these, 13 studies provided data suitable for the calculation of risk ratio (RR), 5 giving psychological outcomes17–21 and 12 non-psychological19 22–32; and 8 provided data for the calculation of standardised mean differences (SMD), 6 giving psychological outcomes21 30 33–36 and 2 non-psychological 29 37. Further six studies did not provide raw data but are included in the results; three each giving psychological outcomes38–40 and non-psychological outcomes 17 41 42.…”
Section: Resultsmentioning
confidence: 99%
“…Further six studies did not provide raw data but are included in the results; three each giving psychological outcomes38–40 and non-psychological outcomes 17 41 42. Meta-analyses were possible on two outcomes: anxiety and depression from eight studies by using standardised mean difference 19–21 30 33–36. Where only RR data were given20 21 conversion to standardised mean difference was undertaken using the Campbell Collaboration calculator (https://campbellcollaboration.org/research-resources/effect-size-calculator.html).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women were at higher risk for depression [18], PTSD [16], and general mental health impairments [8] (1 study each), while men were found to be at higher risk for (non-psychotic) psychological disorder of any kind [19] and at higher risk for alcohol use disorder [20] (1 study each).…”
Section: Gendermentioning
confidence: 99%